Radiocarbon dating (Scottish Historical and Archaeological Internet Reports, 2019)
A sub-circular double-ditched enclosure, visible as a cropmark on aerial photographs, was excavated by CFA Archaeology Ltd in 2013. The enclosure had an inner ditch with two possible entrances and an intermittent outer ditch. The inner ditch measured up to 4.65m wide and survived to a maximum depth of 1.4m. Artefactual and ecofactual assemblages were limited, with the most significant finds being evidence of shale working. Soil micromorphological analysis indicates that both ditches silted up gradually, with their fills derived from re-deposited upcast as well as soil eroding from the surroundings. Radiocarbon dates from waterlogged wood and animal bone found within the ditch fills produced a date range of 1608–204 bc. The paucity of material makes it difficult to be certain of the date and function of the enclosure.